Systematics of African house snakes revisited: News about systematic placement of two former Lamprophis species endemic to the Ethiopian highlands - Tiutenko, Arthur (15th Conference of the Herpetological Association of Africa, 2023)
The systematic affinities of two rare and little-known lamprophiid snakes have been reviewed. One of these species has been long known either as Lamprophis erlangeri or as Boaedon erlangeri. It is endemic to moist montane forest remnants and formerly forested areas in the south and south-west of the Ethiopian highlands. New molecular and morphological data brought evidence that this species has been misplaced in both genera of ‘African house snakes’. A new genus has been described that represents a sister clade to the Western and Central African genera Bothrophthalmus and Bothrolycus from which it differs by general body form and proportions, head shape, number of preocular scales, absence of loreal pits, maxillary dentition as well as by a number of cranial features. The second Ethiopian endemic, Lamprophis abyssinicus, that had been treated in the recent past as a close relative of Lamprophis erlangeri was assigned in the course of this revision to the genus Pseudoboodon on a basis of similar external morphology and cranial osteology.<br
Keywords: Herpetologie